Agammaglobulinemia: causative mutations and their implications for novel therapies. (December 2013) - Berglöf, Anna; Turunen, Janne J; Gissberg, Olof; Bestas, Burcu; Blomberg, K Emelie M; Smith, CI Edvard
Agammaglobulinemias are primary (inherited) immunodeficiencies characterized by the lack of functional B-cells and antibodies, and are caused by mutations in genes encoding components of the pre-B-cell or B-cell receptor, or their signaling pathways. The known genetic defects do not account for all agammaglobulinemic patients, suggesting that novel mutations underlying the disease remain to be found. While efficient, the current life-maintaining therapy with immunoglobulins and antibiotics is non-curative, prompting research into alternative treatment strategies that aim at rescuing the expression of the affected protein, thus giving rise to functional B-cells. These include gene therapy, which could be used to correct the defective gene or replace it with a functional copy. For a number of genetic defects, another alternative is to modulate the splicing of the affected transcripts. While these technologies are not yet ready for clinical trials in agammaglobulinemia, advances in genomic targeting are likely to make this option viable in the near future.